The Frequency of Intrathyroidal Follicular Helper T Cells Varies with the Progression of Graves’ Disease and Hashimoto’s Thyroiditis - Yun Cai; Zhixiao Wang; Xiaoyun Liu; Ling Wei; Shushu Li; Xuqin Zheng; Tao Yang; Xinyu Xu (Journal of Immunology Research)
Objective. Autoimmune thyroid diseases (AITD), mainly Graves’ disease (GD) and Hashimoto’s thyroiditis (HT), are common organ-specific autoimmune diseases characterized by circulating antibodies and lymphocyte infiltration. Follicular helper T (Tfh) cell dysregulation is involved in the development of autoimmune pathologies. We aimed to explore the role of intrathyroidal and circulating Tfh cells in patients with GD and HT. Methods. Ultrasound-guided thyroid fine-needle aspiration (FNA) was conducted in 35 patients with GD, 40 patients with HT, and 22 patients with nonautoimmune thyroid disease (nAITD). Peripheral blood samples were also obtained from 40 patients with GD, 40 patients with HT, and 40 healthy controls. The frequencies of intrathyroidal and circulating Tfh cells from FNA and peripheral blood samples were assessed by flow cytometry. Additionally, the correlations between the frequencies of the Tfh cells and the levels of autoantibodies and hormones or disease duration were analyzed. Results. The frequency of intrathyroidal CD4+CXCR5+ICOShigh Tfh cells was higher in HT patients than in GD patients. Significant correlations were identified between the percentages of circulating and intrathyroidal Tfh cells and the serum concentrations of thyroid autoantibodies, especially thyroglobulin antibodies (TgAb), in AITD. Intrathyroidal CD4+CXCR5+ICOShigh Tfh cells were positively correlated with free triiodothyronine (FT3) in HT patients but negatively correlated with FT3 in GD patients. In addition, HT patients with a longer disease duration had an increased frequency of intrathyroidal CD4+CXCR5+ICOShigh and CD4+CXCR5+PD-1+ Tfh cells. In contrast, in the GD patients, a longer disease duration did not affect the frequency of intrathyroidal CD4+CXCR5+ICOShigh but was associated with a lower frequency of CD4+CXCR5+PD-1+ Tfh cells. Conclusions. Our data suggest that intrathyroidal Tfh cells might play a role in the pathogenesis of AITD and they are potential immunobiomarkers for AITD.